“EVERYBODY NEEDS TO BE DOING SOMETHING”: EXPLORING THE CONTRADICTIONS IN ONTARIO WORKS AND THE NORMATIVE EXPECTATIONS BEHIND THE WORK OF BECOMING ELIGIBLE, EMPLOYABLE AND EMPLOYED - Pennisi, Sarah (My University, 2014)
Since Ontario Works (OW) was implemented in 1998, the policy has been tinkered with including making changes in benefits and relaxing of some of the more punitive practices such as a life time ban for recipients convicted of fraud. However in OW, one ofOntario's social assistance programs, the requirement to participate in work or work preparation activities, remains relatively unchanged. Intended to end the supposed free riding of recipients, work for welfare continues to be an unwavering policy instrument despite findings that the policy is at best ineffective and at worst counterproductive in helping OW clients find and keep work (Lightman et al 2005, Little 2005, Peck 2001, Quaid 2002).
Some scholars argue that administrative practices are maintained by the normative assumptions on which a policy stands (Fraser 1989, George and Wilding 2003, Plant et al. 1989). In order to investigate the normative underpinnings behind OW work, this study explored the literature on welfare state approaches. This review focused on the normative assumptions surrounding work that are engaged to diffuse and inculcate neoliberal imperatives and class and gender related codes of conduct connected to OW work. By conducting interviews with OW clients and staff, this study also examined the ways in which norms facilitate the administration of OW especially how internalized taken-for-granted ideas about work are leveraged by the policy. Gramsci’s notions of hegemony and common sense (Gramsci 2010) and Bourdieu’s notion of habitus, field and capital (Bourdieu 1989) were engaged as theoretical tools that might explain how taken-for-granted assumptions facilitate the administration of OW and the enforcement of workfare policies.
The project found that the 'works' part of OW is comprised of 3 types of work: becoming eligible, employable and employed. A major contradiction that emerged during the investigation is that OW is focused on ensuring ongoing eligibility - not on employment. The administration of OW work engages with normative expectations surrounding work, welfare and gender that are connected to the contradictions in OW work. It is common sense ideas surrounding these normative expectations (such as the moral benefits of work) that maintain practices and reconcile contradictions. As well, a specific habitus (coach/gatekeeper) operates in OW which engages certain types of common sense ideas that align with normative expectations.
Keywords: Ontario Works; Workfare; Welfare; habitus; common sense; Social Policy; Social Welfare; Social Work; Social Policy